2022
DOI: 10.5817/sts2022-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Relative Age Effect in Elite Swimmers in U14 Czech Championship

Abstract: PURPOSE The issue of the Relative Age Effect (RAE) has been studied in the theory of sports for more than 30 years. Most studies concentrate on team sports, while the area of some individual sports like swimming can be considered still underexplored. METHODS The aim of our study was to verify the RAE in young elite swimmers (n = 198) who participated in Czech Republic U14 Championship (1) in male and female samples (2) according to swimming disciplines and distances (3) and performance (times in individual dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…We checked publication bias using the Funnel plot, The Egger’s Regression-Based test, Effect size Estimates for Trim-and-Fill Analysis, and Fail-safe N . The Funnel plot, suggesting a publication bias, is available in Supplementary Figure 1 (Bozděch et al, 2023a). Subsequent funnel plots of subgroups (age period) further showed that publication bias was significantly smaller for soccer players who were older than 19 years of age and slightly lower for 15–19-year-old players.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We checked publication bias using the Funnel plot, The Egger’s Regression-Based test, Effect size Estimates for Trim-and-Fill Analysis, and Fail-safe N . The Funnel plot, suggesting a publication bias, is available in Supplementary Figure 1 (Bozděch et al, 2023a). Subsequent funnel plots of subgroups (age period) further showed that publication bias was significantly smaller for soccer players who were older than 19 years of age and slightly lower for 15–19-year-old players.…”
Section: Resultsmentioning
confidence: 99%
“…The supplementary materials (Bozděch et al, 2023b) encompassed independent results obtained from the studies we researched. These materials included information about the age category, performance level, sex, sample size, and calculated effect size estimation ( w , OR Q1 vs. Q4, OR Q2 versus Q4 , OR Q3 versus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Předložená studie navazuje na naši předchozí práci, kde jsme se zaměřovali na mladé elitní plavce (chlapce a dívky) ve věkové kategorii U14 (Bozděch, Agricola, Křehký, Schlegel, & Zháněl, 2022). Co se týče zjištěných rozdílů mezi jednotlivými studiemi (tzn.…”
Section: Diskuze a Závěryunclassified
“…Given that the literature search yielded no results on CYE in taekwondo articles, we will use the term RAE in this paper. The RAE has been found in many sports and sports categories [ 11 , 12 , 13 , 14 ], but there are also sports where the RAE has not been identified [ 15 ] or in very few cases [ 16 ]. Many studies have found that the RAE mostly exists in male groups of athletes and much less in female groups, as well as a prevalence of RAE in younger categories [ 17 ].…”
Section: Introductionmentioning
confidence: 99%